Jihad and Islam in World War I - Zürcher, Erik-Jan (Debates on Islam and Society, 2016)
This books investigates the background and nature of the Ottoman Jihad proclamation, but also its effects in the wider Middle East. It looks at the German hopes and British fears of a worldwide rising of Muslims in the colonial empires. It also discusses the fierce academic debates caused by the Jihad proclamation, in which the 1915 manifesto of Leiden Islam scholar Christiaan Snouck Hurgronje ("Holy War Made in Germany") played a key role. This title was made Open Access by libraries from around the world through Knowledge Unlatched.